Usage and abusage : a guide to good English - Patridge, Eric, ....- (New York : W.W. Norton, 1997)
An entertaining and useful reference updated for the 1990s is designed to assist the reader in avoiding misuses of the English language when trying to write or speak clearly and directly.
Keywords: Engels ; mondelingen communicatie; Engels ; schriftelijke communicatie; Engels ; taalgebruik